Oxidative Cracking of Aromatic Compounds Related to Lignin Constituents with Steam Using ZrO2Al2O3FeOx Catalyst - Takuya Yoshikawa; Duangkamol Na-Ranong; Teruoki Tago; Takao Masuda (My University, 2010)
The catalytic activity of iron oxide composite catalyst (ZrO2–Al2O3–FeOx) was investigated for converting aromatic compounds derived from plant biomass into useful aromatics. Catalytic cracking of lignin constituent-related di-aromatics such as diphenyl ether, diphenyl methane, and 2-benzyloxyphenol, and mono-aromatics such as guaiacol, acetophenone, and 1-phenyl-1-propanol was carried out over ZrO2–Al2O3–FeOx. The catalytic reactions were conducted in a fixed-bed reactor at 773 K under atmospheric pressure. Diphenyl ether and diphenyl methane were stable, whereas 2-benzyloxyphenol was thermally decomposed, followed by the production of toluene and phenol over ZrO2–Al2O3–FeOx. Guaiacol and acetophenone were selectively converted into 54 C-mol% of phenol and 29 C-mol% of benzene, respectively. The methoxy and carbonyl groups were decomposed into gaseous products mainly consisting of CO2, whereas dehydration of the aliphatic hydroxyl group in 1-phenyl-1-propanol mainly occurred to produce 1-phenyl-1-propene. ZrO2–Al2O3–FeOx catalyst is effective for degrading alkyl ether bonds between aromatic rings, and the ring substituent methoxy and carbonyl groups.
Keywords: Guaiacol; Diphenyl ether; Acetophenone; Cresol; Thermochemical Biomass Conversion Processes